THE ROLE OF SPECIAL EXERCISES IN IMPROVING THE TECHNIQUE OF ROWERS AT THE STAGE OF SPORTS MASTERY DEVELOPMENT - Erkuziyevich, Ruzimatov Islomjon; qizi, Rafiqova Dilnuraxon Xusniddinjon (Research Focus International Scientific Journal, 2026)
This article examines the importance of special exercises and the training process in developing the physical, technical, and psychological preparedness of canoe rowers at the stage of sports mastery development. The research is devoted to studying the effectiveness of training aimed at improving young athletes’ movement accuracy, balance maintenance, rapid reaction, and coordination skills. It highlights the annual training cycle, the dosage of training loads, the step-by-step development of technical and theoretical preparation, and the process of designing training programs adapted to the individual characteristics of athletes. The research results show that the systematic development of athletes’ balance, strength, endurance, and coordination abilities enables them to perform technical movements effectively and adapt quickly to competition conditions.